2012
DOI: 10.1177/1721727x1201000322
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Microbiological and Inflammatory Evidence of the Efficacy of Combination Therapy Including Serratiopeptidase in the Treatment of Periimplantitis

Abstract: The first two authors contributed equally to this workThe present study was aimed to evaluate the effect of introducing administration of the proteolytic enzyme serratiopeptidase in the combined mechanical-antibiotic treatment of periimplantitis (PI). Two randomized groups of 64 adults with a diagnosis of PI were studied over a 6-month period. All patients were treated with a combined mechanical and antibiotic protocol for 15 days. The experimental group (EG) was administered antibiotic and serratiopeptidase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Under this point of view, it’s interesting to understand the effect of SPEP on some physiological aspects of clinical P. aeruginosa strains that are so relevant for the development of chronic infection. Furthermore, the demonstrated ability of SPEP to interfere with the adhesive properties of bacterial pathogens [ 21 , 22 , 23 , 24 ] drives researchers to further investigate its action on other virulence factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this point of view, it’s interesting to understand the effect of SPEP on some physiological aspects of clinical P. aeruginosa strains that are so relevant for the development of chronic infection. Furthermore, the demonstrated ability of SPEP to interfere with the adhesive properties of bacterial pathogens [ 21 , 22 , 23 , 24 ] drives researchers to further investigate its action on other virulence factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of infectious diseases, SPEP is recognized to be effective against a variety of biofilm-associated chronic infections and against adhesion and invasion of bacteria on eukaryotic cells [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Basing on these results, we added SPEP to protocols of combined treatment of PI. More recently, we also demonstrated that the combined systemic administration of antibiotics and SPEP associated to mechanical debridement of implant surfaces significantly enhances success rates in the treatment of PI (19). After 15 years of experience we decided to compare clinical outcomes of this potentially improved protocol with those of other colleagues adopting the standard combined protocol that does not include SPEP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, commercial proteases have also been successful in the eradication of biofilms [ 46 , 47 ]. Serratiopeptidase, a commercially available bacterial metalloprotease has proven to be effective against a variety of biofilm-associated medical conditions due to the following reasons: It can modify the virulent phenotype of bacteria in biofilms [ 48 , 49 ] It is effective against mature biofilms [ 49 ] It enhances the bactericidal effect of antibiotics against bacterial biofilms [ 50 ]. …”
Section: Application Of Serratiopeptidase In Therapeuticsmentioning
confidence: 99%
“…Colonization of bacteria occurs at the surface of the implant, forming a biofim which causes severe inflammation of the peri-implant tissue and damages the implant supporting bone. In a controlled study of 64 adults, [ 50 ] evaluated the combined effect of serratiopeptidase with antibiotics in peri-implantitis. The combined treatment significantly improved clinical, microbiological, and inflammatory parameters as compared to the control group.…”
Section: Application Of Serratiopeptidase In Therapeuticsmentioning
confidence: 99%